2021
DOI: 10.1515/biol-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Blocking circ_UBR4 suppressed proliferation, migration, and cell cycle progression of human vascular smooth muscle cells in atherosclerosis

Abstract: The circ_UBR4 (hsa_circ_0010283) is a novel abnormally overexpressed circRNA in oxidized low-density lipoprotein (ox-LDL)-induced model of atherosclerosis (AS) in human vascular smooth muscle cells (VSMCs). However, its role in the dysfunction of VSMCs remains to be further investigated. Here, we attempted to explore its role in ox-LDL-induced excessive proliferation and migration in VSMCs by regulating Rho/Rho-associated coiled-coil containing kinase 1 (ROCK1), a therapeutic target of AS. Expression of circ_U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…12,36,37 Because of the significant overexpression of circUBR4 in ox-LDL-treated VSMCs, 16 we focused on the ceRNA role of circUBR4 in regulating VSMC migration and proliferation stimulated by ox-LDL. Zhang et al 17 identified that circUBR4 acted as a regulator of VSMC proliferation and migration under ox-LDL by binding to miR-107 to induce ROCK1. Ding et al 19 underscored the regulation of circUBR4 in ox-LDL-evoked VSMC migration and proliferation depending on the modulation of miR-370-3p/HMGB1 axis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,36,37 Because of the significant overexpression of circUBR4 in ox-LDL-treated VSMCs, 16 we focused on the ceRNA role of circUBR4 in regulating VSMC migration and proliferation stimulated by ox-LDL. Zhang et al 17 identified that circUBR4 acted as a regulator of VSMC proliferation and migration under ox-LDL by binding to miR-107 to induce ROCK1. Ding et al 19 underscored the regulation of circUBR4 in ox-LDL-evoked VSMC migration and proliferation depending on the modulation of miR-370-3p/HMGB1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence also indicated that NRP2 functioned as a downstream effector of the circCHFR/ miR-149-5p axis in regulating VSMC migration and proliferation. 31 Recent evidence has uncovered 3 ceRNA networks in the regulation of circUBR4, including the circUBR4/miR-107/ROCK1, 17 circUBR4/miR-370-3p/HMGB1, 19 and circUBR4/miR-133a-3p/PAPPA, 18 in VSMC migration and invasion. The 4 ceRNA axes (including our findings) may be 4 paralleled or interactional networks for the regulation of circUBR4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsa_circ_0001445 reverses ox-LDL‑induced inhibition of HUVEC proliferation by targeting SRSF1 [ 8 ]. Inhibiting circ_UBR4 (hsa_circ_0010283) suppressed the proliferation, migration, and cell cycle progression of human vascular smooth muscle cells and promotes the progression of AS [ 9 ]. Circ_0004104 protects vascular endothelial cells from low-density lipoprotein-induced dysfunction by targeting the miR-328-3p/TRIM14 axis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%